2013
DOI: 10.3109/10253890.2012.744391
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced avoidance learning in behaviorally inhibited young men and women

Abstract: Behavioral inhibition (BI) is a temperamental tendency to avoid or withdraw from novel social and nonsocial situations and has been shown to predispose individuals to anxiety disorders. However, adequate means to assess individual differences in avoidance learning in humans are presently limited. Here, we tested whether individuals with high self-reported BI show faster associative learning on a purely cognitive task, and whether such inhibited individuals are more prone to avoid aversive outcomes. In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 29 publications
7
35
1
Order By: Relevance
“…Previous research indicates the hippocampus may be involved in risk for anxiety in terms of structure [48], function [49], and behavior [19]. Reduced hippocampal activity in the high AMBI group could enhance learning in standard delay (500-ms) conditioning.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research indicates the hippocampus may be involved in risk for anxiety in terms of structure [48], function [49], and behavior [19]. Reduced hippocampal activity in the high AMBI group could enhance learning in standard delay (500-ms) conditioning.…”
Section: Discussionmentioning
confidence: 98%
“…One possibility is that anxious individuals are more sensitive to the cues and contingencies in their environments, resulting in faster learning and better performance on avoidance tasks. This theory is supported by the observation of individual differences in learning in both operant and classical conditioning avoidance paradigms [4][5][6]18,19]. Although operant paradigms may seem more suited to the high cognitive processes typically associated with avoidance, eyeblink classical conditioning is an established and reliable model for understanding human learning.…”
Section: Introductionmentioning
confidence: 91%
“…For example, hippocampal differences have been related to the development of PTSD (Gilbertson et al 2006). Furthermore, behaviorally inhibited individuals show enhanced avoidance in a hippocampal dependent avoidance task (Sheynin et al 2013). It is possible that increased reliance on cerebro-cerebellar circuitry may be the result of hippocampal dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…As such, recent research studies have reported increased resting-state connectivity of the amygdala and insula in Veterans with PTSD, implicating the salience network (Sripada et al 2012). However, given previous research in cerebellarmediated eyeblink conditioning (Caulfield et al 2013(Caulfield et al , 2015, avoidance learning (Sheynin et al 2013), and taskbased fMRI (Blackford et al 2009), we hypothesized that regions in the cerebellum will significantly correlate with executive network resting-state fluctuations, with inhibited individuals demonstrating greater cerebellar connectivity with the executive network.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation